Molecular Epidemiology of Measles Virus before and after the 2003 Mass Vaccination Campaign for Measles/Rubella in Iran - M Naseri; V Salimi; T Mokhtari-Azad; A Esteghamati; MM Gooya; SA Nadji; Z NoroozBabaei; SM Marashi; Z Saadatmand; F Rezaei; R Hamkar; H Triki (Tehran University of Medical Sciences, 2011)
"nBackground: Molecular epidemiology of measles virus (MV) is important, not only to measure the success of measles vaccination programs but also to monitor the circulation and elimination of the virus worldwide. In this study, we compared MV obtained from patients before the 2003 mass vaccination MR campaign and viruses detected after 2003 until 2008 in Iran."nMethods: The nucleoprotein (N) gene of 29 MV strains circulating in Iran between 2002 and 2008 were amplified by RT-PCR and subjected to sequence and phylogenetic analysis."nResults: Molecular characterization of MV studied here revealed that although the outbreaks in Iran were associated with MV genotype D4, the isolated viruses clearly belonged to several different lineages. Maximum and minimum homology within the 29 Iranian strains in our study was100% and 94.9% within the carboxyl terminus of the N gene, respectively. Using ClustalX program, the alignment of Iranian MV sequences showed nine lineages."nConclusion: This study provides the usefulness of MV sequence analysis for the demonstration of local interruption of indigenous strain transmission as well as providing a valuable means for monitoring the elimination processes of MV control.